Combining ability and gene action studies for seed yield, its components and quality traits in bread wheat (Triticum aestivum L. em Thell.) - Ankita Singh, Anil Kumar, Ekhlaque Ahmad, Swati and J.P. Jaiswal (Electronic Journal of Plant Breeding, 2012)
Combining ability for yield, its contributing traits and quality parameters was studied in 15 parental genotypes (12 lines, 3testers) in a line x tester scheme. The purpose of the study was to identify and select superior parents and best hybridcombinations on the basis of estimates of general and specific combining abilities. The differences among genotypes werehighly significant for all the characters studied. Estimates of variance due to general combining ability (gca) and specificcombining ability (sca) and their ratio revealed that both additive and non-additive gene effects were important for differentcharacters studied. The estimates of gca effects as a whole suggested that if most of the traits are to be improved throughhybridization and selection, then priority should be given to parents K 9107 from among the testers and UP 2338*2/4/SNZ/TRAP#/3/KAUZ*2/TRAP//KAUZ from among the lines. (ATTILA*2/STAR)/PBW550 was the best specific crossfor grain yield.